PENELITIAN TINDAKAN KELAS DALAM PEMBELAJARAN BAHASA INDONESIA: MATERI MENULIS DI KELAS VII MTs ALHAKIMIYAH PARINGGONAN - Parapat, Hanifah (CV. Alfa Pustaka, 2024)
This research aims to improve the writing skills of grade VII students of MTs Alhakimiyah Paringgonan through the application of Classroom Action Research (PTK). The problem faced is the low writing ability of students, which can be seen from the lack of skills in composing structured and coherent writing. The method used in this study is PTK which is carried out in three cycles, consisting of planning, action, observation, and reflection. Learning uses project-based approaches and collaborative techniques, such as peer review, to improve students' writing skills. The results of the study showed a significant improvement in students' writing skills. In the first cycle, only 50% of students achieved the minimum completeness criterion (KKM) in writing, while in the second cycle, this figure increased to 70%. In the third cycle, 90% of students managed to achieve KKM, showing very significant progress. The implementation of PTK with a project-based approach also succeeded in increasing student motivation and participation in writing activities, with 85% of students stating that they were more interested and active in learning to write after the second cycle. Thus, this study concludes that PTK can be an effective method in improving students' writing skills at MTs Alhakimiyah Paringgonan.